PENGARUH SISTEM LAYANAN JEMPUT ZAKAT, LAYANAN VIA TRANSFER, LAYANAN KONTER ZAKAT DAN KUALITAS PELAYANAN TERHADAP PREFERENSI MUZAKKI MEMBAYAR ZAKAT DI BAZNAS KOTA MOJOKERTO - Sutiyani, Dina; Galuh, Ajeng Kartika (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study aims to determine the effect of the zakat pick-up service system, transfer service, zakat counter service, and service quality on the preferences of muzakki to pay zakat at BAZNAS Mojokerto City. The approach used in this research is a quantitative approach. The sampling method or respondents from this research is opening 98 muzakki. The data used is taken through the distribution of questionnaires. This study uses a binomial logistic regression analysis technique using a test tool, namely the SPSS 22.0 program. The results showed that simultaneously, the variables of zakat pick-up service (X1), zakat transfer service (X2), zakat counter service (X3) and service quality (X4) had a significant effect on the preference of muzakki to pay zakat (Y). Partially, each variable of zakat pick-up service, zakat transfer service, zakat counter service and service quality has a significant effect on the preferences of muzakki to pay zakat in BAZNAS of Mojokerto City.